Social and Professional Partnership in Preparation of Pedagogical Personnel: Regional Practices - O. V. Tumasheva (Высшее образование в России)
Ensuring the competitiveness of pedagogical universities and their graduates is one of the strategic tasks in the field of education and the country’s economy. Its achievement requires orientation of the basic educational programs and technologies for their implementation to the needs of the modern school. This necessitates a rethinking of approaches to organizing the training of future teachers, strengthening its practical orientation by expanding the area of responsibility of direct employers. The central issue of the article is the role and directions of implementing partnerships between the employer and the pedagogical university in preparing future teachers in the current educational situation. The purpose of this article is to identify promising areas of its development on the basis of an analysis of the existing regional experience in the training of teachers based on the implementation of social and professional partnerships. The study of the role and directions of the implementation of partnerships between the employer and the pedagogical university in the preparation of modern graduates – future teachers was carried out on the basis of the application of theoretical and empirical research methods. An analysis of the role of the employer in the training process was carried out on the basis of questionnaires and expert interviews. The main material was the pedagogical experience of teachers of the Institute of Mathematics, Physics and Informatics of KSPU named after V.P. Astafiev, and employers – directors of educational institutions of secondary education of the Krasnoyarsk Territory and the Republic of Khakassia, as well as the results of a study of the problems of training future teachers. Based on empirical data, the article concludes that social and professional partnerships are a necessary part of the training of future teachers in accordance with modern requirements and standards. The role and directions of implementing partnerships between employers and a pedagogical university in the preparation of future teachers are detailed. The practical significance lies in the use of the results obtained in the system of higher pedagogical education in order to ensure high-quality training of graduates.